The Italian regime of recognition of intercountry adoptions of children in light of the ECHR: what about singles? - Tuo, Chiara Enrica (CUADERNOS DE DERECHO TRANSNACIONAL, 2015)
This paper deals with the compatibility of the Italian regime of recognition of intercountry adoptions of children by single persons with the right to family life enshrined in Art 8 ECHR such as interpreted by the ECtHR, according to which a violation thereof may occur also in cases where familial status established abroad are denied transnational effects. Keywords: intercountry adoption of children, recognition, single persons, Article 8 ECHR, familial status created abroad, cross-border continuity. Riassunto: Il presente contributo affronta la questione della compatibilità del sistema italiano di riconoscimento delle adozioni internazionali di minori da parte dei single con l’art. 8 della CEDU così come interpretato dalla Corte di Strasburgo, secondo la quale una violazione del diritto fondamentale al rispetto della vita familiare può configurarsi anche laddove non sia garantita la continuità transnazionale degli status familiari validamente e stabilmente costituiti all’estero. Parole chiave: adozione internazionale di minori, riconoscimento, single, articolo 8 CEDU, status familiari create all’estero, continuità transnazionale.